Improving Luminescent Performances of Thermally Activated Delayed Fluorescence Conjugated Polymer by Inhibiting the Intra‐ and Interchain Quenching. Issue 10 (12th March 2018) - Zhu, Yunhui; Yang, Yike; Wang, Yanjie; Yao, Bing; Lin, Xingdong; Zhang, Baohua; Zhan, Hongmei; Xie, Zhiyuan; Cheng, Yanxiang
Abstract: Suppressing emission quenching is still a real issue for thermally activated delayed fluorescence (TADF) materials as the emitters generally tend to aggregate in condensed film, leading to deteriorating performance in devices. In contrast to the TADF small molecules adopting host–guest systems, polymers possess the advantage that the TADF chromophore can be chemically dispersed into the backbone and thus the quenching process can be inhibited effectively. Here, a strategy applied to the conjugated polymer is presented, in which a TADF chromophore with controlled content is embedded into the backbone of polycarbazole through its donor moiety. The oligomeric carbazole segment acts as the role of "blocking segment, " suppressing the intra‐ and interchain interactions. The polymers therefore exhibit superior photoluminescence quantum yield of up to 92.1%. More importantly, the efficiency roll‐offs of the relevant devices are significantly reduced, offering an external quantum yield (EQE) of 15.6% even at luminance of 1000 cd m −2, corresponding to 92.3% to the maximum EQE. Abstract : Carbazole oligomer acts as the role of "blocking segment" in the thermally activated delayed fluorescence (TADF) conjugated polymers, suppressing the intra‐ and interchain quenching processes and therefore improving luminescent performances of the polymers.